Analysis of Aroma Characteristics of Traditional and Wild Dianhong Congou Black Tea - Miao NIU; Xiongyu LI; Hongyan YANG; Yuqi HE; Yawen XU; Jiahua LI (Shipin gongye ke-ji)
To clarify differences in the aroma components and characteristics between traditional and wild Dianhong Congou black teas, five traditional and five wild Dianhong Congou black teas were investigated using headspace solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) to measure and analyze the aroma characteristics of the two types of tea. A total of 180 aroma components were detected in the 10 tea samples, including 31 alcohols, 19 ketones, 33 aldehydes, 32 esters, 11 acids, 35 hydrocarbons, and 19 other categories. Thirty-six components with odor activity values greater than 1 were identified in traditional Dianhong Congou and wild Dianhong Congou black teas, with nine components common to both. Linalool was found to be the major contributor to aroma in traditional Dianhong Congou black tea, which was characterized by a floral and sweet aroma, while linalool, hexanal, and nonanal were the most significant aroma components in wild Dianhong Congou black tea, which had floral, sweet, woody, and fruity aromas. The results of this study provide a data reference for understanding the aroma characteristics of traditional and wild Dianhong Congou black teas.